2021
DOI: 10.3389/fendo.2021.595894
|View full text |Cite
|
Sign up to set email alerts
|

Levoketoconazole in the Treatment of Patients With Cushing’s Syndrome and Diabetes Mellitus: Results From the SONICS Phase 3 Study

Abstract: BackgroundCushing’s syndrome (CS) is associated with numerous comorbidities, including diabetes mellitus (DM). Levoketoconazole, an orally administered ketoconazole stereoisomer, is in clinical trials for the treatment of CS.MethodsSONICS, a prospective, open-label, phase 3 study in adults with confirmed CS and mean 24-h urinary free cortisol (mUFC) ≥1.5× ULN, included dose-titration, 6-month maintenance, and 6-month extension phases. This subanalysis evaluated the efficacy of levoketoconazole in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…At the end of the maintenance phase, normalization of mUFC was observed in 34% and 25% of patients with and without diabetes mellitus, respectively, without a dose increase during the maintenance phase. In addition, the measures of glycemic control, HbA1c and fasting blood glucose levels, were improved in both subgroups, but change was more pronounced in patients with diabetes mellitus (Figure 5) [71].…”
Section: Efficacy In a Subgroup Of Patients With Type 2 Diabetes Mellitusmentioning
confidence: 97%
See 1 more Smart Citation
“…At the end of the maintenance phase, normalization of mUFC was observed in 34% and 25% of patients with and without diabetes mellitus, respectively, without a dose increase during the maintenance phase. In addition, the measures of glycemic control, HbA1c and fasting blood glucose levels, were improved in both subgroups, but change was more pronounced in patients with diabetes mellitus (Figure 5) [71].…”
Section: Efficacy In a Subgroup Of Patients With Type 2 Diabetes Mellitusmentioning
confidence: 97%
“…Normalization of cortisol is sufficient, in some cases, to improve glycemic control and may also reverse diabetes [2,70]. In SONICS, efficacy and safety of levoketoconazole in patients with CS and diabetes mellitus (36 patients) were evaluated as exploratory analyses [71]. At the end of the maintenance phase, normalization of mUFC was observed in 34% and 25% of patients with and without diabetes mellitus, respectively, without a dose increase during the maintenance phase.…”
Section: Efficacy In a Subgroup Of Patients With Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…A subgroup analysis of patients with diabetes mellitus showed mean UFC normalization with levoketoconazole was similar in patients with and without diabetes mellitus; some patients were able to lower the dose of their diabetes medication(s); and improvements were observed in LDL-C, weight, body mass index, and waist circumference. 16,17…”
Section: Comparative Efficacymentioning
confidence: 99%
“…On the basis of these promising results on glucose metabolism, levoKTZ was studied in 94 patients affected by CS in a phase III, open-label, multicenter clinical trial (SONICS study), which found UFC normalization in 46% and 33% of patients with diabetes mellitus and without diabetes mellitus, respectively. Interestingly, in diabetic patients, who were adequately controlled at baseline, levoKTZ treatment led to a clear amelioration of glycometabolic control (i.e., glycated hemoglobin decreased from 6.9% to 6.2%), and a decrease in glycated hemoglobin (i.e., from 5.5% to 5.3%) was noted even in non-diabetic patients [ 94 ]. In addition, after the 6-month maintenance period, a significant decrease in body weight, peripheral edema and acne and hirsutism in women as well as an improvement in quality of life and depressive status was observed [ 94 , 95 ].…”
Section: Medical Therapy Of Mild Hypercortisolismmentioning
confidence: 99%
“…Interestingly, in diabetic patients, who were adequately controlled at baseline, levoKTZ treatment led to a clear amelioration of glycometabolic control (i.e., glycated hemoglobin decreased from 6.9% to 6.2%), and a decrease in glycated hemoglobin (i.e., from 5.5% to 5.3%) was noted even in non-diabetic patients [ 94 ]. In addition, after the 6-month maintenance period, a significant decrease in body weight, peripheral edema and acne and hirsutism in women as well as an improvement in quality of life and depressive status was observed [ 94 , 95 ]. These data now need to be confirmed in the phase III, double-blind, multicenter clinical trial (LOGICS study) that was started in September 2017 to assess the efficacy and safety of levoKTZ treatment in CS patients, of which no preliminary data have been available so far ( ; accessed date: 21 October 2021).…”
Section: Medical Therapy Of Mild Hypercortisolismmentioning
confidence: 99%